The Implementation of Independent Attitude for Children with Cerebral Palsy at SKH Negeri 01 Kota Serang - Rr Dina Kusuma Wardhani (Universitas Syiah Kuala, 2025)
Implementing Independence in Children with Physical Disabilities and Cerebral Palsy at SKH Negeri 01 Serang City. This study aims to explore the implementation of independence in children with physical disabilities and cerebral palsy at SKH Negeri 01 Kota Serang. Independence is a critical skill to enhance the quality of life for children with special needs. This research employed a qualitative approach, using observation, interviews, and documentation. The findings revealed that fostering independence involves training daily living skills, using assistive devices, and conducting confidence-building activities. Challenges include communication barriers and insufficient information about the children's capabilities. The study recommends collaboration among teachers, parents, and the community to optimally support the development of these children.